Clinico-Epidemiological Profile And Factors Affecting Severity Of Atopic Dermatitis In North Indian Chilldren - Sarkar Rashmi; Kanwar Amrinder J (Indian Journal of Dermatology, 2004)
Atopic dermatitis (AD) is a chronic, relapsing dermatitis commonly affecting children. Various epidemiologic factors and clinical patterns of the same were evaluated in 125 patients out of 418 attending the pediatric dermatology clinic over a period of 11/2 years. Of these, 26 were infants (upto 1 year of age) and 99 were children. Mean duration of the disease in the infantile group was 3 months while in the childhood group it was 6 years. In the infantile group, family history of atopy was found in 11 patients (42.3%), while in the childhood group 35 (35.35%) had family history of atopy, 7 (7.07%) had personal history of atopy and 2 (2.02%) had both personal and family history of atopy. The infantile group had more frequent facial involvement and acute type of eczema, while in the childhood type, site involvement was less specific and chronic type of eczema was more frequent. Most of the patients had mild to moderate degree of severity of the disease.